Maintenance of T cell function in the face of chronic antigen stimulation and repeated reactivation for a latent virus infection. - Mackay, L; Wakim, L; van Vliet, C; Jones, C; Mueller, SN; Bannard, O; Fearon, D; Heath, W; Carbone, F (2012)
Persisting infections are often associated with chronic T cell activation. For certain pathogens, this can lead to T cell exhaustion and survival of what is otherwise a cleared infection. In contrast, for herpesviruses, T cells never eliminate infection once it is established. Instead, effective immunity appears to maintain these pathogens in a state of latency. We used infection with HSV to examine whether effector-type T cells undergoing chronic stimulation retained functional and proliferative capacity during latency and subsequent reactivation. We found that latency-associated T cells exhibited a polyfunctional phenotype and could secrete a range of effector cytokines. These T cells were also capable of mounting a recall proliferative response on HSV reactivation and could do so repeatedly. Thus, for this latent infection, T cells subjected to chronic Ag stimulation and periodic reactivation retain the ability to respond to local virus challenge.